Building Internalization of Early Childhood Learning through Collaborative Learning - Zahid Zufar At Thaariq; Khoirunnisa Khoirunnisa; Risma Chulashotud Diana (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
The context of teaching and learning in the era of the COVID-19 pandemic provides more space for families to teach their children, especially at an early age. Therefore, the purpose of this study is to examine the phenomenon of family-based early childhood learning starting from literature studies, problems to solutions in overcoming these problems. The solution that is the key to successful learning in the family environment is the internalization of what parents teach their children. The author uses a collaborative learning design in its application. This solution will direct the child to find a learning style that suits him. This is certainly beneficial for parents in making it easier to teach their children. Therefore, it is hoped that the existence of this research study can be an alternative reference for parents in teaching their children, especially at the early age level which is the rapid development of the brain in receiving various external information around it.